(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this article a phytocenotic analysis of species of the family Dracocephalum in the flora of Uzbekistan has been provided. The study indicated nine communities of Dracocephalum species in the Pskom, Ugam, Chatkal, and Nurata, Turkestan ridges of the Western Tien Shan between 2016 and 2020.